2021
DOI: 10.1002/cbdv.202001002
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as a Biocompatible Mild Anti‐Inflammatory Supplement for Animal Feed and Agricultural Fields

Abstract: Biochar is an organic material and high in carbon content, besides its use for energy purposes, it is also a material that serves the purpose of improving soil fertility, organic matter content of soils and removing heavy metals from water and soil. This study aims to investigate the antimicrobial effects of biochar whose beneficial effects on agricultural productivity has been proven by different studies. Scientific literature concerning the antibacterial, antifungal, and antiviral effects of the apricot seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…In this study, a combination of 6 μg/mL AgNPs with different concentrations of biochar was made to assess its activity against colorectal cancer cell lines as well as against pathogenic bacteria. Our results showed that biochar had no effect on the growth of either Gram-positive or Gram-negative bacteria, suggested that biochar may have an indirect antimicrobial effect, via altering some bacteria’s metabolic processes [ 28 , 30 , 31 ]. In contrast, AgNPs suppressed the growth of S. epidermidis , S. aureus , E. coli , P. aeruginosa and P. aeruginosa ATCC 10145.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a combination of 6 μg/mL AgNPs with different concentrations of biochar was made to assess its activity against colorectal cancer cell lines as well as against pathogenic bacteria. Our results showed that biochar had no effect on the growth of either Gram-positive or Gram-negative bacteria, suggested that biochar may have an indirect antimicrobial effect, via altering some bacteria’s metabolic processes [ 28 , 30 , 31 ]. In contrast, AgNPs suppressed the growth of S. epidermidis , S. aureus , E. coli , P. aeruginosa and P. aeruginosa ATCC 10145.…”
Section: Discussionmentioning
confidence: 99%
“…Feed-grade biochar is primarily added to feed at a rate of 0.1–4.0% of the daily feed intake (Man et al 2021 ; O’Toole et al 2016 ). As shown in Table 5 , adding biochar to feed has the potential to increase feed intake and weight gain (Mirheidari et al 2020 ; Sivilai et al 2018 ); improve animal health (Bolan et al 2021 ; Yıldızlı et al 2021 ); facilitate toxin and contaminant detoxification, increase nutrient intake, decrease antibiotic residues, and decrease enteric methane release (Man et al 2021 ; Schmidt et al 2019b ; Toth et al 2016 ).…”
Section: Animal Farmingmentioning
confidence: 99%
“…Due to increasing awareness of people toward natural ingredients, apricots and their by-products are attractive to various industries and fields of research. As a result, the apricot kernel helps in boosting skin health, improving metabolism, enhancing vision, reducing the risk of diabetes, and maintaining digestive functioning [ 88 ]. Therefore, it is well known across the globe to produce various cosmetics (face masks, scrubs, creams, lotions) and food (snacks, oatmeal, muffins, scones, salads, vegan, and animal cruelty-free personal grooming items).…”
Section: Market Value Of Apricot Kernelmentioning
confidence: 99%